Development of efficient targeted insertion mediated by CRISPR-Cas12a and homology-directed repair in maize - Barco, Brenden; Dong, Shujie; Matsuba, Yuki; Crook, Ashley; Xu, Ruiji; Zhang, Yingxiao; Zhang, Chengjin; Carlin, Ryan; Potter, Kevin; Rigoulot, Stephen B.; Park, Jeongmoo; Seaberry, Erin M.; et al. (Frontiers in Genome Editing, 2025)
Targeted insertion (TIN) of transgenic trait cassettes has the potential to reduce timeline and cost for GM product development and commercialization. Precise genome engineering has made remarkable progress over the last several decades, particularly with the use of site-directed nucleases as core editing machinery. However, there are still many critical factors that can impact TIN efficiency including insertion site selection, nuclease optimization and expression, donor vector design, gene delivery, and stable event regeneration. Here, we develop workflows for target site sequence identification and gRNA screening for CRISPR-Cas12a system and demonstrate its successful application for TIN in maize with donor sequences up to 10 kilobase pairs (kb) in size. We first prioritize genomic regions for inserting transgenes in silico using bioinformatics tools and then test gRNA performance using a leaf protoplast transient assay. Despite its known low efficiency, we identify homology-directed repair (HDR) as the preferential pathway for directing targeted insertions of large sequences in immature embryos and demonstrate double-junction integrations at a rate of up to 4%. We further apply a molecular analysis workflow using large amplicon TaqMan assays and nanopore sequencing for streamlined identification and characterization of high-quality insertion events with intact large inserts. Analysis of TIN events across generations suggests that efficiency bottlenecks are not limited to donor targeted integration; attrition in efficiency also results from partial or additional donor insertion, chimerism, and close linkage with undesired sequence insertions such as those encoding the editing machinery. This work represents a major step forward in realizing the potential of precise genome engineering in maize for basic research and biotech trait development applications.